Pengaruh Brand Image, Harga, dan Fashion Lifestlye Terhadap Keputusan Pembeli Pakaian Thrift Shop Kota Bandung (Studi Pada Bisnis Thrift Lugpreloved) - Daffa Fauzan Adriansyah; Dedi Gumilar (eCo-Buss, 2024)
This study's goal is to confirm the impact of brand image, price and fashion lifestyle on purchasing decisions. The research was carried out utilizing a quantitative approach that combines description and verification techniques. Data collection techniques were collected from questionnaire answers, interview literature studies. In obtaining 100 adequate samples, this study used 3,500 populations controlled by utilizing the Slovin formula. Based on the results of the assumption test using the SPSS 23 program, it can be concluded that brand image shows a significant influence on purchasing decisions, with a t-value of 2.796 and a significance level of 0.006. Meanwhile, price also has a significane effect on purchasing decisions, as indicated by a t-value of 3.755 with a significant level of 0.000. And fashion lifestyle also has a noteworthy impact on decisions to buy, with a t-value of 2.567 and a significan level of 0.009. Simultaneously, these three factors make an important contribution to purchasing decisions, as evidenced by a f-value of 51.321 and a very significant p-value of 0.000.